2008
DOI: 10.1128/aem.00409-08
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Salmonella enterica serovar Heidelberg from Turkey-Associated Sources

Abstract: Salmonella enterica serovar Heidelberg strains are frequently associated with food-borne illness, with recent isolates showing higher rates of resistance to multiple antimicrobial agents. One hundred eighty S. enterica serovar Heidelberg isolates, collected from turkey-associated production and processing sources, were tested for antimicrobial susceptibility and compared by pulsed-field gel electrophoresis (PFGE) and plasmid profile analysis. The potential for the transfer of resistance between strains was stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 22 publications
5
39
0
3
Order By: Relevance
“…When S. Heidelberg isolates from human patients were compared to those of the major food animal species, there was extensive overlap in PFGE profiles, plasmid types, and antimicrobial susceptibility profiles, indicating a lack of host restriction among S. Heidelberg genotypes (203,217,218). In a study examining the core genomes of the population structure of many of the prominent serovars, it was concluded that the genomes of S. Heidelberg isolates were likely shaped by a high degree of horizontal genetic transfer (219).…”
Section: Examples Of Salmonella Host Range In Chicken-related Serovarsmentioning
confidence: 99%
See 1 more Smart Citation
“…When S. Heidelberg isolates from human patients were compared to those of the major food animal species, there was extensive overlap in PFGE profiles, plasmid types, and antimicrobial susceptibility profiles, indicating a lack of host restriction among S. Heidelberg genotypes (203,217,218). In a study examining the core genomes of the population structure of many of the prominent serovars, it was concluded that the genomes of S. Heidelberg isolates were likely shaped by a high degree of horizontal genetic transfer (219).…”
Section: Examples Of Salmonella Host Range In Chicken-related Serovarsmentioning
confidence: 99%
“…This presents the possibility for coselective pressure, with antimicrobial use selecting for enhanced virulence, or conversely, the increased ability of these bacteria to survive iron-limited environments in the host could select for resistance to one or more antimicrobials (83,84). S. Heidelberg plasmids also contain genes encoding disinfectant and heavy metal resistance, which may provide a selective advantage for survival in the avian production environment where pathogen control strategies are employed (84,218).…”
Section: Examples Of Salmonella Host Range In Chicken-related Serovarsmentioning
confidence: 99%
“…Annual costs for Salmonella control efforts are estimated to be $14.6 billion (Scharff, 2010;Heithoff et al, 2012). Salmonella is not only a public health concern due to the number of cases per year, but many strains have developed resistance to antimicrobial agents (Kim et al, 2005;Foley & Lynne, 2008;Bajpai, Baek, & Kang, 2012) due to continued therapeutic use of antimicrobials in feed products (Su, Chiu, Chu, & Ou, 2004;Kim et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the tendency of S. Heidelberg to cause severe extra-intestinal infections (Wilmshurst & Sutcliffe, 1995) such as myocarditis and septicemia (Vugia et al, 2004), the occurrence of S. Heidelberg multidrug resistance strains is of extreme clinical importance. Salmonella Heidelberg strains exhibiting antimicrobial resistance have been isolated from humans, retail meats and food animals (Logue, Sherwood, Olah, Elijah, & Dockter, 2003;Nayak et al, 2004;Kaldhone et al, 2008;Zhao et al, 2008;Lynne, Kaldhone, David, White, & Foley, 2009;Oloya, Doetkott, & Khaitsa, 2009;Han et al, 2011). Studies suggest that poultry-associated S. Heidelberg strains harbor IncFIB, IncA/C, IncH2, and IncI1 plasmids, which may contain genes that confer resistance to several antibiotics such as tetracycline, kanamycin, streptomycin, and sulfonamides (Han et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…International trade in frozen turkey meat may also be a hazard (Mondini and Gasparini, 1964) and in 1996 an outbreak of S. Agona linked with pre-cooked turkey meat was reported (Synnott et al, 1998). Closely related S. Heidelberg strains have been found in turkeys and in human cases (Hird et al, 1993;Kaldhone et al, 2008) but similar strains have also been identified in egg production, which may be a more likely source (Zhao et al, 2008). S. Agona linked with turkeys has also been reported (Doublet et al, 2004), but this is a widespread serovar which has also been linked to contaminated soya bean meal so could have multiple origins.…”
Section: Salmonella Serovars In the Turkey Meat Production Chainmentioning
confidence: 99%